2017
DOI: 10.5194/cp-13-231-2017
|View full text |Cite
|
Sign up to set email alerts
|

Tropical forcing of increased Southern Ocean climate variability revealed by a 140-year subantarctic temperature reconstruction

Abstract: Occupying about 14 % of the world's surface, the Southern Ocean plays a fundamental role in ocean and atmosphere circulation, carbon cycling and Antarctic ice-sheet dynamics. Unfortunately, high interannual variability and a dearth of instrumental observations before the 1950s limits our understanding of how marine–atmosphere–ice domains interact on multi-decadal timescales and the impact of anthropogenic forcing. Here we integrate climate-sensitive tree growth with ocean and atmospheric observations on southw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 80 publications
(173 reference statements)
1
35
0
1
Order By: Relevance
“…there is also a significant relationship between these sub-Antarctic spring and summer temperatures and the Niño 3 region in the tropical Pacific (Turney et al 2017).…”
Section: Temperature Trends In the Extratropical Southern Hemispherementioning
confidence: 95%
See 1 more Smart Citation
“…there is also a significant relationship between these sub-Antarctic spring and summer temperatures and the Niño 3 region in the tropical Pacific (Turney et al 2017).…”
Section: Temperature Trends In the Extratropical Southern Hemispherementioning
confidence: 95%
“…Nearby, New Zealand has experienced similar temperature increases; the National Institute of Water and Atmospheric Research (NIWA) has produced two different temperature time series to show country-wide temperature changes. One is a seven-station series (Salinger 1981) Elsewhere in the mid-latitudes, a temperature reconstruction was created for a 140-year period at Macquarie and Campbell, two island stations south of New Zealand (Turney et al 2017). The authors found that there was a significant increase in variability beginning in the 1940s, with increasing westerly winds across the Southern Ocean and a maximum pressure gradient in austral summer.…”
Section: Temperature Trends In the Extratropical Southern Hemispherementioning
confidence: 99%
“…8), Ninnis Glacier underwent a major retreat in the 1940s (Frezzotti et al, 1998) and there was a switch from dominant outlet glacier retreat across the wider region in the 1970s and 80s to cooler conditions 325 and glacier advance from 1990 to 2010 (Miles et al, 2013). A similar change in wind pattern may also be reflected in temperature reconstructions from 1870 to 2010 in the New Zealand subantarctic islands, which lie directly between the Cook-Ninnis-Mertz region and New Zealand, where there is an abrupt switch towards a more variable climate from the 1940s onwards (Turney et al, 2017). Evidence of such variability is also recorded in wind direction 330 at the nearest research station, Dumont d'Urville, where there was an abrupt shift in the 1990s towards more easterly winds (Fig.…”
mentioning
confidence: 79%
“…When breeding, seabirds are central place foragers, which increases potential niche overlap among species (Connan et al 2014) and their co-existence is made possible by differences in the timing of breeding (Cooper et al 2001), diet (Ridoux 1994) and foraging and nesting locations (Weimerskirch et al 1986). Despite our understanding of the incubation and chick-rearing stages, it is less clear how resource partitioning is achieved in the energetically critical pre-laying period of egg formation (Moreno et al 2008, Sorensen et al 2009 or how this partitioning may be disrupted under what have been observed to be rapidly changing environmental conditions (Le Roux and McGeoch 2008, Constable et al 2014, Turney et al 2017, McQuaid 2018.…”
Section: Introductionmentioning
confidence: 99%